Penegakan Hukum Lingkungan dalam Pengelolaan Limbah Bahan Berbahaya dan Beracun (B3) - Puannandini, Dewi Asri; Nurhidayatulloh, Muhammad Miftah; Soheh , Ruhiyat (Universitas Pahlawan Tuanku Tambusai, 2025)
Environmental law enforcement in the management of Hazardous and Toxic Waste (B3) is a crucial aspect to protect the quality of the environment and public health in Indonesia. This study examines the effectiveness of the implementation of laws and regulations, especially Law Number 32 of 2009 concerning Environmental Protection and Management, in regulating the management of B3 waste by various industrial sectors. The research method used is normative juridical with an analysis of legal regulations and law enforcement practices in the field. The results of the study indicate that there are still gaps in the implementation of the law, where many business actors have not fully complied with the obligation to manage B3 waste according to the established standards, thus potentially causing environmental pollution and health risks. Criminal and administrative sanctions stipulated in the law are not fully effective in encouraging compliance, so that increased supervision, education, and strict sanctions are needed. This study recommends a more comprehensive and participatory law enforcement strategy to ensure that B3 waste management is carried out in accordance with legal provisions in order to create a healthy and sustainable environment.